Huanglian Jiedu Decoction ameliorates DSS-induced colitis in mice via the JAK2/STAT3 signalling pathway - Zhuo Lu; Wanna Xiong; Simeng Xiao; Yilong Lin; Kai Yu; Guihua Yue; Qiaoming Liu; Fang Li; Jianqin Liang (Chinese Medicine, 2020)
Abstract Background Ulcerative colitis (UC) is an intestinal disease which was characterized by intestinal inflammation, mucosal injury and fibrosis. In this paper, the effect of Huanglian Jiedu Decoction (HJD), a well-known traditional Chinese medicine with significant anti-inflammatory effect, on dextran sulphate sodium (DSS)-induced UC in mice and inhibition of JAK2/STAT3 pathway were investigated. Methods BALB/c mice were randomly divided into 6 groups: HJD group (high, medium and low dose), USAN group, UC group, and control group. UC in mice were induced through free access to 3% DSS solution. After being treated with HJD for 8 days, all animals were sacrifice. Pathological examination of colonic specimen was performed by H&E staining. Cytokines (TNF-α, IL-6, and IL-1β) in colon were assayed by ELISA and immunofluorescence, MPO in colon and ATT in serum were detected by ELISA. Moreover, mice in HJD group and UC group were treated with AG490 to inhibit the expression of JAK2 protein, then the expression of JAK2 and STAT3 protein in colon was determined by western blotting and immunofluorescence staining. Furthermore, KI67 in colon was examined by immunohistochemistry, and apoptosis was detected by TUNEL staining, and collagen deposition was assayed by Masson staining after JAK2/STAT3 pathway in UC mice was inhibited by HJD. Results After mice being treated with HJD, the symptoms (weight loss and haematochezia) of UC were alleviated, and the contents of inflammatory cytokines (TNF-α, IL-6 and IL-1β) and MPO in colon were significantly decreased. The expression of JAK2 and STAT3 protein was reduced after administration with HJD. After JAK2/STAT3 pathway being inhibited with HJD, the cell apoptosis, collagen deposition and immunoreactivity of macrophage in colon were significantly reduced, but the expression of Ki67 was markedly enhanced in both UC group and HJD group compare with control group. Conclusions HJD treatment can alleviate intestinal mucosal damage and has the protective effect on UC by downregulating JAK2 and STAT3 expression to reduce inflammation via JAK2/STAT3 pathway.